The investigation of serum vaspin levels in atherosclerotic coronary artery disease - Kobat, M. A.; Yavuzkir, M. F.; Dagli, M. N.; Celik, A.; Bulut, M.; Baydas, A.; Balin, M. (Oxford Univ Press, 2011)
[Abstract Not Available]